INDOL-3-CARBINOL IN THE TREATMENT OF BENIGN BREAST DISORDERS - E. T. Zulkarnayeva; R. H. Hakimova; Ye. A. Lapan; I. L. Blagodetelev (Опухоли женской репродуктивной системы)
123 patients with various forms of fibrocystic mastopathy (n=114) and fibroadenoma of mammry gland (n=9) were enrolled into the study. Indol-3-carbinol (indinol, Close corporation «Mirax-Pharma») was administered in the dose of 300—400 mg per day for 3—6 months. Disappearance of complaints to pain was observed in 35% of patients after 3 months of therapy and in 63% — after 6 months of therapy. Objective signs of fibrocystic mastopathy completely regressed in 9% of patients after 3 months of therapy and in 16% — after 6 month of therapy. Overall considerable improvement of condition or complete cure was seen in 55% of patients after 3 month of treatment and in 92% — after 6 months of therapy. Thus, indinol is highly effective and safe agent for treatment of different types of mastopathy.